2014
DOI: 10.1021/np400672g
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Clerodane Diterpenes from Zuelania guidonia

Abstract: The leaves of Zuelania guidonia yielded eight new clerodane diterpenes, namely, zuelaguidins A-H (1-8), and the known clerodane diterpene esculentin A (9). Some of these structures contained a 3,6-dihydro-1,2-dioxin moiety. The new compounds were isolated and identified using 1D- and 2D-NMR experiments. All compounds were evaluated for cytotoxicity against the CCRF-CEM (human acute lymphocytic leukemia), CEM-ADR5000 (human acute lymphocytic leukemia resistant to doxorubicin), and MIA-PaCa-2 (human pancreatic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 43 publications
1
25
0
Order By: Relevance
“…The structures of zuelaguidins A–D ( 17–20 ) from Z. guidonia are typical of this subtype. 16 Corymbulosins A–C ( 25–27 ) from Laetia corymbulosa were elucidated as clerodane diterpenes unsaturated at C-3, C-13(16), and C-14. 18 Corymbulosin A ( 25 ) has a decadienoate ester at C-2, while corymbulosins B and C ( 26–27 ) have a saturated decanoate ester at C-6.…”
Section: Structure Classifications and Sources Of Clerodane Diterpmentioning
confidence: 99%
See 2 more Smart Citations
“…The structures of zuelaguidins A–D ( 17–20 ) from Z. guidonia are typical of this subtype. 16 Corymbulosins A–C ( 25–27 ) from Laetia corymbulosa were elucidated as clerodane diterpenes unsaturated at C-3, C-13(16), and C-14. 18 Corymbulosin A ( 25 ) has a decadienoate ester at C-2, while corymbulosins B and C ( 26–27 ) have a saturated decanoate ester at C-6.…”
Section: Structure Classifications and Sources Of Clerodane Diterpmentioning
confidence: 99%
“…For example, esculentin A ( 76 ) has been reported in both ent–neo 16 and neo 32 configurations. In addition, while caseargrewiin A ( 74 ) was shown as a neo -clerodane, caseargrewiins B–D ( 1256–1258 , structures in Section 3.5) co-isolated from C. grewiifolia were shown as ent-neo -clerodanes.…”
Section: Structure Classifications and Sources Of Clerodane Diterpmentioning
confidence: 99%
See 1 more Smart Citation
“…Casearin J (CJ; Figure 1a ) is a tricyclic clerodane diterpene found in Casearia sylvestris , a plant from the Salicaceae family. We have previously reported that representatives of this class of secondary plant metabolites are preferentially cytotoxic to leukemia cells 16 and that they directly inhibit the SERCA pump. 17 However, the exact mechanism of cytotoxicity and the reason for their preference toward leukemia cells remain poorly understood.…”
mentioning
confidence: 99%
“…The leaves of Zuelania guidonia yielded clerodane DE called zuelaguidins E (92) and G (93). [106] Tigliane-type diterpenoid called crotusin C (94) was isolated from the methanolic extract of the twigs and leaves of Croton caudatus. [107] The data on the biological activity of DEs are given in table 4.…”
Section: Diterpenoid Endoperoxides (De) Derived From Algae Liverwortmentioning
confidence: 99%